Sentiment Analysis of Chairperson’s Message and Its Influence on Financial Performance : Study on NIFTY 50 Companies - Jena, Manoj Kumar; Das, Srikant; Kar, Brajaballav (Indian Journal of Finance, 2024)
Purpose : Return on assets (ROA) is one of the most important financial parameters used for multi-level analysis. The investment in assets also depends on the future perspective of the management, which is reflected in the chairperson’s message in the annual reports. Thus, the chairperson’s message is likely to indicate future investments in assets and expected returns from such assets. The message is important for the investors as this is one of the major sources of qualitative information about the business strategy. However, the information the business managers share may include selective information from a strategic perspective. Are there any tendencies in the language used in the message by the chairpersons as well as the accompanying sentiments? How does a company’s overall perception evolve? How has the worldwide epidemic influenced chairpersons’ messages? Design/Methodology/Approach : The study investigated these questions using the information from the annual reports of the top 50 companies (NIFTY 50) listed in the National Stock Exchange of India. The methodology of this study is mostly grounded on text mining, text analytics, and regression analysis. Findings : The negative tones in the chairperson’s speech did not show much significance for the future performance of NIFTY50 companies. However, the positive sentiments did have an impact and were significantly associated with the ROA of the companies. Practical Implications : The paper would add value to the academicians, researchers in the area of NLP and text analytics, and the investors’ community who access the annual reports for making investment decisions. Originality : The use of text analytics to understand sentiments and apply them to elicit a deeper understanding of the company’s strategy is a novel attempt.